The Role of PPARs in Lung Fibrosis - Heather F. Lakatos; Thomas H. Thatcher; R. Matthew Kottmann; Tatiana M. Garcia; Richard P. Phipps; Patricia J. Sime (PPAR Research)
Pulmonary fibrosis is a group of disorders characterized by accumulation of scar tissue in the lung interstitium, resulting in loss of alveolar function, destruction of normal lung architecture, and respiratory distress. Some types of fibrosis respond to corticosteroids, but for many there are no effective treatments. Prognosis varies but can be poor. For example, patients with idiopathic pulmonary fibrosis (IPF) have a median survival of only 2.9 years. Prognosis may be better in patients with some other types of pulmonary fibrosis, and there is variability in survival even among individuals with biopsy-proven IPF. Evidence is accumulating that the peroxisome proliferator-activated receptors (PPARs) play important roles in regulating processes related to fibrogenesis, including cellular differentiation, inflammation, and wound healing. PPARα agonists, including the hypolidipemic fibrate drugs, inhibit the production of collagen by hepatic stellate cells and inhibit liver, kidney, and cardiac fibrosis in animal models. In the mouse model of lung fibrosis induced by bleomycin, a PPARα agonist significantly inhibited the fibrotic response, while PPARα knockout mice developed more serious fibrosis. PPARβ/δ appears to play a critical role in regulating the transition from inflammation to wound healing. PPARβ/δ agonists inhibit lung fibroblast proliferation and enhance the antifibrotic properties of PPARγ agonists. PPARγ ligands oppose the profibrotic effect of TGF-β, which induces differentiation of fibroblasts to myofibroblasts, a critical effector cell in fibrosis. PPARγ ligands, including the thiazolidinedione class of antidiabetic drugs, effectively inhibit lung fibrosis in vitro and in animal models. The clinical availability of potent and selective PPARα and PPARγ agonists should facilitate rapid development of successful treatment strategies based on current and ongoing research.